Study on the Behavior of Cement Slurry Prepared by Vibration Agitation and Numerical Simulation of Flow Field - Ziming Kou; Tianyi Tan; Haotian Cui (Buildings)
Vibration agitation, a mechanically enhanced material mixing technique, is appropriate for preparing concrete- and other cement-based materials as it helps to eliminate the agglomeration effect between particles, improving mixing efficiency and material properties and saving resources. Applying vibration agitation to the large-scale industry is challenging primarily due to the difficulty in elucidating the microscopic mixing mechanism. To this end, the Euler multiphase flow model and ALE dynamic grid technology were combined to create the flow field simulation model of the cement slurry vibration mixing process in this paper. The physical parameters and mixing characteristics of various structure agitators under various vibration mixing frequencies were investigated as well. The findings demonstrated that vibration agitation significantly improved the mixing effect and the mixing efficiency and homogeneity were positively correlated with the excitation frequency. The slurry had a larger average velocity and turbulent kinetic energy, along with a reduced frictional viscous moment on the agitator. The vibration altered the system’s pressure field and fluid movement direction. Furthermore, the improvement of the flow field parameters for the horizontal shaft mixer was highly sensitive in the low-frequency range, whereas for vertical shaft agitators, it was at higher excitation frequencies that more significant gains were achieved.